Highlighting the Relevance of CD8+ T Cells in Filarial Infections - Kwarteng, Alexander; Asiedu, Ebenezer; Koranteng, Kelvin Kwaku; Asiedu, Samuel Opoku (Frontiers in Immunology, 2021)
The T cell immune responses in filarial infections are primarily mediated by CD4+ T cells and type 2-associated cytokines. Emerging evidence indicate that CD8+ T cell responses are important for anti-filarial immunity, however, in co-infections could be suppressed. This review summarizes what we know so far about the activities of CD8+ T cell responses in filarial infections, co-infections and the associations with the development of filarial pathologies.